2021
DOI: 10.1155/2021/5588176
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxide Sludge/Hydrochar-Fe Composite Catalysts for Photo-Fenton Degradation of Dyes

Abstract: The photo-Fenton oxidation process was employed to degrade methylene blue (MB) using a hydroxide sludge/hydrochar-Fe composite as a catalyst prepared by physical activation of raw hydroxide sludge from a drinking water treatment plant and hydrochar-Fe prepared by hydrothermal carbonization from two-phase olive mill waste. The prepared composite was characterized by XRD, SEM, EDS, ICP, and FT-IR. The effect of major parameters, including pH, H2O2 concentration, and a dose of composite on the removal of MB has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In the present study, NC was compared with other reported solid materials for adsorption and photo-Fenton catalytic degradation of MB as indicated in Table S5 [2,5,[73][74][75][76][77][78][79].…”
Section: Comparison Between Nc and Other Adsorbents And Catalystsmentioning
confidence: 99%
“…In the present study, NC was compared with other reported solid materials for adsorption and photo-Fenton catalytic degradation of MB as indicated in Table S5 [2,5,[73][74][75][76][77][78][79].…”
Section: Comparison Between Nc and Other Adsorbents And Catalystsmentioning
confidence: 99%
“…The removal efficiency of MB using various Fenton catalysts is demonstrated in table 1. Hydroxide sludge/hydrochar-Fe composite 95.00 [18] Iron ore tailing from the tailings dam 80.00 [19] Magnetic nanocomposite 46.00 [20] Iron oxide supported on activated carbon 98.00…”
Section: H2o2 → •Oh + Oh −mentioning
confidence: 99%
“…It is classified as an acutely toxic compound and a mutagenic substance in the GHS classification [17][18][19][20]. In previous studies on degrading dyeing wastewater, MO was often selected as the modeling pollutant for evaluation of catalysts [21,22].…”
Section: Introductionmentioning
confidence: 99%